Publicación de la ‘Colección Villasante de cantos y música tradicional ashaninka (1981-1985)’ y proyecto de investigación - Villasante Cervello, Mariella (2023)
As in all hunter-gatherer societies, beliefs associated with the spiritual world and the musical arts are very important among the Ashaninka, the Nomatsiguenga and all Amazonian native peoples. These themes have been little studied in social anthropology. Moreover, the relative neglect of the native languages has led to a decrease in the transmission of the beliefs and music that represent the core of the Ashaninka cultural heritage. In this context, my current research aims to shed light on the evolution of the relationship between musical production, beliefs and ethnic identity and, at the same time, to revalue the musical and mythological heritage of the Ashaninka and their ethnic identities. The starting point of this study of social and musical anthropology are the songs that I collected between 1981 and 1985, the Villasante Collection of traditional Ashaninka music archived at the Centre de Recherches d’Ethnomusicologie (CREM, France) which I present in this Note.